Multiomic analysis of oral keratinocytes chronically exposed to shisha. (15th February 2019) - Patil, Shankargouda; Patel, Krishna; Advani, Jayshree; Subbannayya, Tejaswini; Rajagopalan, Pavithra; Babu, Niraj; Solanki, Hitendra; Bhandi, Shilpa; Sidransky, David; Chatterjee, Aditi; Gowda, Harsha; Ferrari, Marco
Abstract : Background: Tobacco is smoked in different form including cigarettes and water pipes. One popular form of water pipe smoking especially in Middle Eastern countries is shisha smoking. Shisha has been associated with various diseases including oral cancer. However, genomic alterations and gene expression changes associated with chronic shisha exposure have not been previously investigated. Objectives: Whole‐exome sequencing and gene expression profiling of immortalized human oral keratinocytes (OKF6/TERT1) cells chronically treated with 0.5% shisha extract for a period of 8 months was undertaken to characterize molecular alterations associated with shisha exposure. Methods: Genomic DNA and RNA were extracted and preprocessed as per manufacturer's instruction and subjected to whole‐exome and transcriptome sequencing using Illumina HiSeq2500 platform. Exome was analyzed using GATK pipeline whereas RNA‐Seq data was analyzed using HiSat2 and HTSeq along with DESeq to elucidate differentially expressed genes. Results: Whole‐exome sequence analysis led to identification of 521 somatic missense variants corresponding to 389 genes RNA‐Seq data revealed 247 differentially expressed genes (≥2‐fold, P‐ value<0.01) in shisha treated cells compared to parental cells. Pathway analysis of differentially expressed genes revealed that interferon‐signaling pathway was significantly affected. We predict activation of MAPK1 pathway which is known to play a key role in oral cancer. We also observed allele specific expression of mutant LIMA1 based on RNA‐Seq dataset. Conclusion: Our findings provide insights into genomic alterations and gene expression pattern associated with oral keratinocytes chronically exposed to shisha.